A Review of Sustainability Reporting Tools (SRTs) for Communities - Siew, Renard Yung Jhien (International Journal of Sustainable Construction Engineering and Technology, 2014)
Sustainability reporting tools (SRTs) for Communities is part of a new paradigm to aid local governments and councils in their decision making process.  These integrative tools have evolved from prior versions of SRTs that focus purely on a single building performance to consider the sustainability performance of communities.  This paper provides a review of mainstream SRTs for Communities, in particular: BREEAM for Communities; LEED for Neighbourhood Development; CASBEE for Urban Development; Green Star for Communities; Sustainability Tool for Assessing and Rating (STAR); EcoCity; and HQE2R.  A critique of these tools is provided to better understand some of the existing limitations including the lack of clarity in the size of development that these SRTs are capable of assessing; lack of published reasoning behind the allocated scores or weightings for the criteria selected; inadequate account of the different sources of uncertainty; the adoption of a static perspective; and the lack of acknowledgement of possible interaction or correlation between criteria.  This review will be of interest to practitioners, academics and developers who are concerned about ways to improve the sustainability of the built environment.